2015
DOI: 10.1016/j.mrfmmm.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Controlled exposure to diesel exhaust and traffic noise – Effects on oxidative stress and activation in mononuclear blood cells

Abstract: 3-h exposure to DE caused no genotoxicity, oxidative stress or inflammation in PBMCs, whereas exposure to noise might cause oxidatively damaged DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 44 publications
(55 reference statements)
3
30
0
1
Order By: Relevance
“…Moreover, there were no significant changes in gene expression of oxidative stress response, DNA repair and inflammation genes, although the variation was rather high and the 95% CI of the relative changes within the PBMCs was substantial. This is in keeping with our findings of no significant effect from 3h of controlled exposure to diesel exhaust at 300 µg/m 3 on gene expression of HMOX1 , OGG1 , IL8 and TNF in PBMCs from young healthy subject ( 37 ). Similarly, 3h of controlled exposure to wood smoke at 354 µg/m 3 or a week’s exposure to much higher levels in a reconstructed Viking age house showed no change in the expression of these genes ( 32 , 45 ), although OGG1 expression was enhanced after 4h of exposure to wood smoke at similar levels ( 36 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, there were no significant changes in gene expression of oxidative stress response, DNA repair and inflammation genes, although the variation was rather high and the 95% CI of the relative changes within the PBMCs was substantial. This is in keeping with our findings of no significant effect from 3h of controlled exposure to diesel exhaust at 300 µg/m 3 on gene expression of HMOX1 , OGG1 , IL8 and TNF in PBMCs from young healthy subject ( 37 ). Similarly, 3h of controlled exposure to wood smoke at 354 µg/m 3 or a week’s exposure to much higher levels in a reconstructed Viking age house showed no change in the expression of these genes ( 32 , 45 ), although OGG1 expression was enhanced after 4h of exposure to wood smoke at similar levels ( 36 ).…”
Section: Discussionsupporting
confidence: 92%
“…We have earlier shown that vanadium and chromium in PM 2.5 personally monitored for 48h was associated with oxidatively damaged DNA in young healthy subjects in Copenhagen, Denmark ( 15 ). On the other hand, we have also studied groups of young (aged 13–19 years) subjects in the hours after controlled exposure to pure diesel exhaust or wood smoke at 300 µg/m 3 PM for 3h without finding any effects on SB or FPG-sensitive sites ( 30 , 36 , 37 ). The lack of effect of these exposures is not likely to be due to too early sampling of the blood samples as such because a recent study of a whole week exposure of wood smoke at very high level in a reconstructed Viking age house also showed no change in oxidatively damaged DNA, although some markers of monocyte adhesion to the vessel wall were changed ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Noise may also cause short term vasoconstriction and in the longer term atherosclerosis due to metabolic changes [ 11 ]. There may be some overlap in mechanisms as oxidative damage has also been observed after traffic noise exposure in mononuclear blood cells in laboratory conditions [ 41 ]. For effects on the brain it is postulated that particles may activate pro-inflammatory cytokines in human macrophages initiating an inflammatory response and oxidative stress and fine particles may be directly absorbed into the nervous system through the olfactory bulb [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with related medical studies, the findings emphasize the impact of cohort and environmental characteristics on obesity, particularly those associated with exposures, a view of green space in an urban area on the one hand, and traffic noise and a view of a highway and an internal road on the other. Referring to traffic noise, for example, by exposing 18 respondents to traffic noise in the laboratory, Hemmingsen et al, (2015) found oxidative stress and damage to the DNA. Referring to sleeping disorders, Bodin et al, (2015) found a reduction in the level of reported sleeping annoyance in housing units with a quiet side than those having at least one window facing a yard, garden or green space With the exception of traffic noise, the findings further indicate gender differences with respect to the former variables, namely, building exposures and green space, and the latter variables, namely, a view of a highway and an internal road.…”
Section: Business and Economic Researchmentioning
confidence: 99%